Microplastic in Marine Environment and Its Impact - Wibowo, Yudha Gusti; Maryani, Anis Tatik; Rosanti, Dewi; Rosarina, Desy (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2019)
This article was the result of a research of literature study sources and impact of microplastic in the marine environment. Plastic debris could make microplasric caused by ultraviolet and give some negative impact for marine environment. Plastic debris in marine environment has come from industrial and fishing activities (human activities). All of marine environment in the world has contaminated by microplastic, microplastic will give negative impact for marine biota, recent study inform that turtle and fish have high microplastic content in both them.plastics industries should take responsibility for the end-of-life oftheir products by introducing plastic recycling or upgrading programmers.